We Are Family: Effects of a Relationship-Strengthening Prevention Intervention on Parenting Behaviors Among Black and Latino Adolescent Couples. (July 2023) - Diaz, Valen R.; Albritton, Tashuna; Katague, Marina; Dancy, Victoria; Breny, Jean M.; Kershaw, Trace
Relationship strain or dissolution between new parents can affect the co-parenting relationship and parenting engagement. The purpose of this study was to evaluate the effect of a relationship-strengthening intervention on parenting behaviors among adolescent couples. Data from a pilot randomized control trial conducted with predominantly Black and Latino couples were analyzed using repeated measures analysis of variance. Observed intervention * time effects and intervention * time * gender effects were not statistically significant, but had small to moderate effect sizes. Intervention couples demonstrated increased parenting sense of competence compared to control couples. Gender differences in intervention effects were observed for both parenting experiences and parenting engagement. Given the pilot nature of the study, these findings provide preliminary evidence of the effectiveness of this couple-based intervention for improving parenting outcomes. Future research should assess the intervention in a larger sample and leverage technology-based approaches as methods for content delivery.